Spontaneous Phase and Morphology Transformations of Anodized Titania Nanotubes Induced by Water at Room Temperature - Wang, Daoai; Liu, Lifeng; Zhang, Fuxiang; Tao, Kun; Pippel, Eckhard; Domen, Kazunari (Nano letters, 2011)
We report a spontaneous phase transformation of titania nanotubes induced by water at room temperature, which enables the as-anodized amorphous nanotubes to be crystallized into anatase mesoporous nanowires without any other post-treatments. These mesoporous TiO2 nanomaterials have a markedly improved surface area, about 5.5 times than that of the as-anodized TiO2 nanotubes, resulting in a pronounced enhanced photocatalytic activity. The present approach not only allows a flexible control over the morphology of TiO2 nanostructures but can fundamentally eliminate the need for high temperature operations for crystallizing amorphous TiO2.